Compreensão de construções passivas em crianças com perturbação do espectro do autismo - Costa, Raquel; Lobo, Maria (Revista da Associação Portuguesa de Linguística, 2020)
This investigation aims to study the comprehension of passives in children with Autism Spectrum Disorder (ASD). Research on passives is sparse and remains inconclusive. Fourteen Portuguese speaking children with ASD (between ages 7 and 13), including children with low and high non-verbal IQ, were compared to four typically developing (TD) children. The comprehension of various types of passives (short vs long, eventive vs psychological) was assessed via a picture selection task. Most children with ASD showed difficulties with passive constructions as compared to controls and to previous studies with Portuguese TD children. The results are in line with the ones we find in studies with this population conducted in other languages. Furthermore, difficulties with passives were dissociated from nonverbal abilities.